Comparison of osteogenic capability of 3D-printed bioceramic scaffolds and granules with different porosities for clinical translation - Yue, Xusong; Zhao, Liben; Yang, Jun; Jiao, Xiaoyi; Wu, Fanghui; Zhang, Yan; Li, Yifan; Qiu, Jiandi; Ke, Xiurong; Sun, Xiaoliang; Yang, Xianyan; Gou, Zhongru; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Pore parameter, structural stability and filler morphology of artificial implants are key factors influencing the process of bone tissue repair. However, the extent to which each of these factors contributes to bone formation in the preparation of porous bioceramics is currently unclear, with the two often being coupled. Herein we prepared the Mgdoped wollastonite (Mg-CSi) scaffolds with 57% and 70% porosity (57-S and 70-S) via 3D printing technique.Meanwhile, the bioceramic granules (57-G and 70-G) with curved pore topography (IWP) were prepared by physically disrupting the 57-S and 70-S scaffolds, respectively, and compared for in vivo osteogenesis at 4, 10 and 16 weeks. The pore parameters, mechanical and biodegradable properties of different porous bioceramics were characterized systematically. The four groups of porous scaffolds and granules were then implanted into a rabbit femoral defect model to evaluate the osteogenic behavior in vivo. The 2D/3D reconstruction and histological analysis showed that significant bone tissue production was visible in the center zone of porous granule groups at the early stage but bone tissue ingrowth was slower in the porous scaffold groups. The bone tissue regeneration and reconstruction capacity were stronger after 10 weeks, and the porous architecture of 57-S scaffold was maintained stably at 16 weeks. These experimental results demonstrated that the structure-collapsed porous bioceramic is favorable for early-stage osteoconduction and the 3D topological scaffolds may provide more structural stability for bone tissue growth for a long-term stage. These findings provide the new ideas for the selection of different types of porous bioceramics for clinical bone repair.